Formulation and in vitro evaluation of natural gum-based microbeads for delivery of ibuprofen (2013)
Purpose: To investigate the effectiveness of three natural gums, namely albizia, cissus and khaya gums, as excipients for the formulation of ibuprofen microbeads. Methods: Ibuprofen microbeads were prepared by the ionotropic gelation method using the natural gums and their blends with sodium alginate at various concentrations using different chelating agents (calcium chloride, zinc chloride, calcium acetate and zinc acetate) at different concentrations. Microbeads were assessed for their morphology using SEM, swelling characteristics, drug entrapment efficiencies, release properties and drug release kinetics. Results: The natural gums alone could not form stable microbeads in the different chelating agents. Stable small spherical discrete microbeads with particle size of 1.35 ± 0.11 to 1.78 ± 0.11 mm, were obtained using the blends of natural gum: alginate at total polymer concentration of 2% w/v using 10% w/v calcium chloride solution at a stirring speed of 300 rpm. The encapsulation efficiencies of the microbeads ranged from 35.3 to 79.8 % and dissolution times, t15 and t80 increased with increase in the concentration of the natural gums present in the blends. Controlled release was obtained for over 4 h and the release was found to be by a combination of diffusion and erosion mechanisms from spherical formulations. Conclusion: The three natural gums would be useful in the formulation of ibuprofen microbeads and the type and concentration of natural gum in the polymer blend can be used to modulate the release properties of the microbeads.